Tinjauan Yuridis Penerbitan Sertifikat Tanah tanpa Surat Pernyataan Pelepasan Hak Atas Tanah (SPPHT) dari Pemilik Tanah Sebelumnya - Muhammad Fandi Asnan; Siti Mahmudah (UNES Law Review, 2023)
There was a land dispute problem in Parit Village which led to a fight over land ownership by the first party as the owner of the land certificate without being accompanied by a Statement of Relinquishment of Land Rights (SPPHT) from the second party as the previous owner. The purpose of this research is to find out the procedures for land registration using the SPPHT from the previous owner and the legal consequences that arise as a consequence of the absence of the SPPHT in making certificates. In this study, the research method used is juridical-normative. The data collection technique used in this research is literature study, namely by focusing on appropriate legal sources. The results of the study show that in the procedure for registering land certificates for the transfer of land rights, the SPPHT has an important position as one of the conditions that must be met by both parties. The existence of SPPHT is necessary to ensure the validity and legal certainty in making land certificates. However, if the SPPHT is not included in the process of making land certificates, it can result in the issuance of multiple certificates. This can have an impact on the existence of sanctions given to the parties involved in the problem.